Parametric Study on the Influence of Embedded SPR to the Performance of Square CFST Columns - Abdul Azim, Abdullah; Azrul, Abdul Mutalib; Shahrizan, Baharom; Wan Hamidon, Wan Badaruzzaman (Penerbit UTHM, 2020)
Steel plate reinforcements (SPR) embedded into the concrete core of a concrete filled steel tube (CFST) column is a promising strengthening scheme. However, further study is required to understand the influence SPR on the strength and behaviour of a CFST column. Numerical models of the CFST columns are developed using finite element analysis. The models are verified with experimental results from past research. The models are in good agreement with the experimental study. Then, a parametric study is conducted to investigate the strength and behaviour of CFST columns embedded with variousconfiguration of SPR. In which, the embedded SPR varies in quantity, thickness and height. The parametric study indicates that these factors have positive influence on the performance of the CFST columns. The performance of the columns is measured in terms of strength, stiffness and ductility. Results have shown that the performance of the columns increases with every increment of the quantity, thickness and height of SPR.